Inflammatory bowel disease in chronic granulomatous disease: An emerging problem over a twenty years' experience. Issue 8 (21st December 2017) - Angelino, Giulia; De Angelis, Paola; Faraci, Simona; Rea, Francesca; Romeo, Erminia Francesca; Torroni, Filippo; Tambucci, Renato; Claps, Alessia; Francalanci, Paola; Chiriaco, Maria; Di Matteo, Gigliola; Cancrini, Caterina; et al.
Abstract: Background: Chronic granulomatous disease (CGD) is a primary immunodeficiency of phagocytes, characterized by life‐threatening infections and hyperinflammation. Due to survival improvement, inflammatory bowel disease (IBD) is becoming increasingly relevant. Here, we report our 20 year experience. Methods: We retrospectively analyzed clinic, endoscopic, and histologic features, as well as the management of CGD‐IBD patients referred to the Bambino Gesù Children's Hospital in Rome, Italy. Results: Of 20 patients with CGD, 9 presented with CGD‐IBD at diagnosis and/or during follow‐up. Symptoms occurred at a median age of 16 years (range 3.2‐42), with a median delay of 6 months for endoscopic confirmation. Patients mainly complained of nonspecific diarrhea (55%), with discrepancy between symptom paucity and severe endoscopic appearance, mainly represented by extensive colonic involvement (44%). Histology revealed at least 2 characteristic features (epithelioid granulomas, pigmented macrophages, and increased eosinophils) in 78% of patients. Eight of 9 patients received oral mesalamine, and 5 required systemic steroids. One patient received azathioprine due to steroid dependence. No patient required biological therapy or surgery. Clinical remission was obtained in all patients, but the majority complained of mild relapses. Two episodes of severe infection occurred early after steroid therapy. Conclusions: Penetrance of CGD‐IBD increases with age. Clinical manifestations may be subtle, and clinicians should have a low threshold to recommend endoscopy. Treatment with NSAIDs and/or steroids achieves a good response, but relapses usually occur. Infection surveillance is mandatory during treatment, to prevent opportunistic infections. A close collaboration between pediatric immunologists and gastroenterologists is pivotal, including combined follow‐up.